The Strange Case of Teaching English Through the Gothic Novel - Maggi, Simona (The Grove - Working Papers on English Studies, 2019)
In this article I endeavour to encourage teachers of Secondary Education to use English literature in their English language lessons. Indeed, literature provides a huge amount of authentic reading materials, making the students practise extensive as well as intensive reading, which is crucial for the foreign language acquisition. Moreover, it is an enormous source of motivation, allowing students to give free rein to their imagination and enjoy their English lessons. The election of gothic fiction is linked to this latter purpose: the 19th gothic genre is generally well accepted by adolescents as it represents a way to reflect on themselves through a journey to “self-revelation”. The double personality/identity-theme of R. L. Stevenson’s novel The Strange Case of Dr Jekyll and Mr Hyde fits well into their interests and their quest for self-knowledge. It offers them the chance to process what they are going through in this often unstable stage of their journey into adulthood by trying to figure out their place in the world. Keywords: Reading skill, Literature in ELT, Gothic fiction, R. L. Stevenson, The Strange Case of Dr Jekyll and Mr Hyde, Double identity